Causality Orientations at Work Scale in the Finnish Working Context - Petri Karkkola; Anja H. Olafsen; Hallgeir Halvari (Scandinavian Journal of Work and Organizational Psychology)
The purpose of this study was to translate the original Norwegian Causality Orientations at Work Scale (COWS) into Finnish and to examine the psychometric properties and criterion validity of the translated measure. A heterogenous sample of Finnish employees (N = 641) completed the Finnish COWS and measures of basic psychological need satisfaction, intrinsic motivation, amotivation, vigour, and exhaustion. In confirmatory factor analysis, fit of the expected three-factor structure of autonomy, control, and impersonal causality orientations was mostly below acceptable. According to the modification indices, estimating several residual covariances would have improved fit. In exploratory structural equation modelling (ESEM), fit of the three-factor model with estimated but minimized cross-loadings was mostly satisfactory to good. The ESEM model demonstrated between-groups measurement invariance at levels from configural to residual invariance and excellent criterion-related validity with the focal measures. The Finnish COWS is a good translation of the original measure that can be used in research with caution. Its further development, especially regarding potentially problematic vignettes and items, is facilitated by the information provided by modification indices and cross-loadings discussed in the present study.